Design and development on automated pneumatic bumper driven by brake actuation / Anand Ganason - Anand, Ganason (2018)
The key concern of this project is the design and development of the technology of pneumatics which plays a major role in the field of automation, modern machine shops and space robots. The aim is to develop a control system based on intelligent and electronically controlled pneumatic bumper and braking system. This project consists of ultrasonic transmitter and receiver circuit, control unit, solenoid valve, pneumatic bumper system and pneumatic braking system. The ultrasonic sensor senses the obstacle closer to the vehicle (within 4-7 feet), then the control signal is given to the pneumatic bumper as well as pneumatic braking system simultaneously. This bumper and braking system is activated only when the vehicle speed is above 40-50 km per hour. This vehicle speed is sensed by the ultrasonic sensor and it is given to the control unit. The control unit controls the solenoid valve so that the pneumatic bumper and braking system is actuated.